Behind COVID-19: Deepening Poverty in Cuba - Tedesco, Laura (2020)
The article explores the Cuban government's reaction to COVID-19, emphasising its control of the press and the role of the Revolutionary Armed Forces (FAR). The main question is whether the health crisis could empower or weaken the government vis-à-vis civil society.